2006
DOI: 10.1093/hmg/ddi467
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and overlapping alterations in motor and sensory neurons in a mouse model of spinal muscular atrophy

Abstract: Motor neuron degeneration is the predominant pathological feature of spinal muscular atrophy (SMA). In patients with severe forms of the disease, additional sensory abnormalities have been reported. However, it is not clear whether the loss of sensory neurons is a common feature in severe forms of the disease, how many neurons are lost and how loss of sensory neurons compares with motor neuron degeneration. We have analysed dorsal root ganglionic sensory neurons in Smn-/-;SMN2 mice, a model of type I SMA. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 27 publications
6
60
1
Order By: Relevance
“…Interestingly, Jablonka et al (Jablonka et al, 2006) recently reported that sensory neuron terminals in the footpads of SMN2 +/+ ;mSmn −/− (severe SMA) embryos are smaller. The difference in sensory neuron terminal size observed in severe SMA embryos is smaller the difference in motor neuron terminal size.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jablonka et al (Jablonka et al, 2006) recently reported that sensory neuron terminals in the footpads of SMN2 +/+ ;mSmn −/− (severe SMA) embryos are smaller. The difference in sensory neuron terminal size observed in severe SMA embryos is smaller the difference in motor neuron terminal size.…”
Section: Discussionmentioning
confidence: 99%
“…Smn-/-;SMN2 mice, a model for type I SMA, show no loss of L5 DRG neurons at the time of severe paralysis; however, nerve endings in the skin are thinner and unlike controls do not reach the outer epidermal layer [36] . In addition, cultured sensory neurons from these mice have shorter neurites, smaller growth cones, and decreased ␤ -actin protein and mRNA in the distal axon.…”
Section: Involvement Of Sensory Axonsmentioning
confidence: 98%
“…In severely affected neonates sensory and motor nerves may become inexcitable [8]. Axonal degeneration of sural nerves, posterior roots, spinal ganglia, ascending tracts, lateral geniculate corpus and thalamus have been reported [40,43], suggesting that the pathology predominates in but is not confined to the motor neurons.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%